An antibacterial dental light-cured glass-ionomer cement with improved hardness. Issue 18 (1st September 2020) - Chen, Yong; Caneli, Gulsah; Almousa, Rashed; Wen, Xin; Anderson, Gregory G.; Xie, Dong
Abstract: An antibacterial dental light-cured glass-ionomer cement has been developed and evaluated. An antibacterial furanone derivative was synthesized and covalently attached onto the surface of alumina filler particles. The formed antibacterial fillers were then mixed into a light-curable glass-ionomer cement formulation. Surface hardness and bacterial viability were used to evaluate the modified cements. Effects of coated furanone moiety content on the modified fillers, modified alumina filler particle size and loading, and total glass filler content were investigated. Results showed that increasing antibacterial furanone content, modified particle size and loading, and total glass filler content generally increased surface hardness. Increasing furanone moiety, filler loading and total filler content increased antibacterial activity. On the other hand, increasing particle size decreased antibacterial activity. The leaching tests indicate that the modified experimental cement showed no leachable antibacterial component to bacteria and cells